2022
DOI: 10.1177/08850666211073598
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Brivaracetam in the Management of Acute Seizures in the Hospital Setting: A Scoping Review

Abstract: Background Clinical considerations for drug treatment of acute seizures involve variables such as safety, tolerability, drug-drug interactions, dosage, route of administration, and alterations in pharmacokinetics because of critical illness. Therapy options that are easily and quickly administered without dilution, well tolerated, and effective are needed for the treatment of acute seizures. The objective of this review is to focus on the clinical considerations relating to the use of intravenous brivaracetam … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 70 publications
(97 reference statements)
0
6
0
Order By: Relevance
“…16,17 However, in other studies, levetiracetam, lacosamide, and valproate were well tolerated at higher rates of administration and in higher doses. [18][19][20][21][22][23][24][25][26] The relatively high doses underscore the need of an "adequately high" first dose, which is approximately two thirds to three quarters of the full loading dose (exact mg/kg doses are presented in Table 2) used for treatment of convulsive SE to minimize the number of false negatives. Furthermore, the medication is also administered within a relatively short period of time to cause a high peak concentration in cerebrospinal fluid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16,17 However, in other studies, levetiracetam, lacosamide, and valproate were well tolerated at higher rates of administration and in higher doses. [18][19][20][21][22][23][24][25][26] The relatively high doses underscore the need of an "adequately high" first dose, which is approximately two thirds to three quarters of the full loading dose (exact mg/kg doses are presented in Table 2) used for treatment of convulsive SE to minimize the number of false negatives. Furthermore, the medication is also administered within a relatively short period of time to cause a high peak concentration in cerebrospinal fluid.…”
Section: Discussionmentioning
confidence: 99%
“…The doses recommended for levetiracetam and valproate are the same as those in prospective studies on SE 16,17 . However, in other studies, levetiracetam, lacosamide, and valproate were well tolerated at higher rates of administration and in higher doses 18–26 . The relatively high doses underscore the need of an “adequately high” first dose, which is approximately two thirds to three quarters of the full loading dose (exact mg/kg doses are presented in Table 2) used for treatment of convulsive SE to minimize the number of false negatives.…”
Section: Discussionmentioning
confidence: 99%
“…BRV is one of the substances that rapidly penetrates the blood–brain barrier, and its bioavailability is almost 100% [ 66 , 68 ]. The drug is metabolized in the liver with the involvement of CYP450, particularly CYP2C9 and CYP2C19 [ 69 , 70 ].…”
Section: Pharmacological Agentsmentioning
confidence: 99%
“…Animal data suggests that brivaracetam may be effective in the treatment of refractory status epilepticus [32]. Several real-world experience studies of brivaracetam in refractory and super-refractory SE have shown SE cessation in approximately one-third of patients [37]. SE cessation is more likely with higher doses given early (e.g., 2 mg/kg initial dose) [37].…”
Section: Brivaracetammentioning
confidence: 99%
“…Several real-world experience studies of brivaracetam in refractory and super-refractory SE have shown SE cessation in approximately one-third of patients [37]. SE cessation is more likely with higher doses given early (e.g., 2 mg/kg initial dose) [37]. Animal data also suggest efficacy in IGE.…”
Section: Brivaracetammentioning
confidence: 99%